Chloroorganiczne zanieczyszczenia środowiska a wskaźnik AOX = Chlorinated organic pollutants of environment and AOX index - Gąsiorek, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The classification, properties and importance of chlorinated organic compounds as environmental pollutants were discussed. It was indicated that the chromatographic methods are the only ones to complete analysis of chloroorganic pollutants in environmental samples. It was shown that the easiest way for assessment of environmental hazard state by these pollutants can be through a AOX index.
Keywords: zanieczyszczenia chloroorganiczne; halogenowane węglowodory; adsorbowalne związki halogenoorganiczne; AOX; chlorinated pollutants; halogenated hydrocarbons; adsorbable halogenatedorganic compounds